Leukotriene B(4) is essential for selective eosinophil recruitment following allergen challenge of CD4(+) cells in a model of chronic eosinophilic inflammation - Cheraim, Alessandra Bonacini; Xavier-Elsas, Pedro; Oliveira, Sandra Helena Penha de [UNESP]; Batistella, Tiago; Russo, Momtchilo; Gaspar-Elsas, Maria Ignez; Cunha, Fernando Queiroz (Pergamon-Elsevier B.V. Ltd, 2008)
Subcutaneous heat-coagulated egg white implants (EWI) induce chronic, intense local eosinophilia in mice, followed by asthma-like responses to airway ovalbumin challenge. Our goal was to define the mechanisms of selective eosinophil accumulation in the EWI model. EWI carriers were challenged i.p. with ovalbumin and the contributions of cellular immunity and inflammatory mediators to the resulting leukocyte accumulation were defined through cell transfer and pharmacological inhibition protocols. Eosinophil recruitment required Major Histocompatibility Complex Class It expression, and was abolished by the leukotriene B4 (LTB4) receptor antagonist CP 105.696, the 5-lipoxygenase inhibitor BWA4C and the 5-lipoxygenase activating protein inhibitor MK886. Eosinophil recruitment in EWI carriers followed transfer of: a) CD4(+) (but not CD4(-)) cells, harvested from EWI donors and restimulated ex vivo; b) their cell-free supernatants, containing LTB4. Restimulation in the presence of MK886 was ineffective. CC chemokine receptor ligand (CCL)5 and CCL2 were induced by ovalbumin challenge in vivo. mRNA for CCL17 and CCL11 was induced in ovalbumin-restimulated CD4(+) cells ex vivo. MK886 blocked induction of CCL17 Pretreatment of EWI carriers with MK886 eliminated the effectiveness of exogenously administered CCL11, CCL2 and CCL5. In conclusion, chemokine-producing, ovalburnin-restimulated CD4(+) cells initiate eosinophil recruitment which is strictly dependent on LTB4 production. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: eosinophils; leukotrienes; chemotaxis; inflammation; chemokines